2021
DOI: 10.1002/er.6854
|View full text |Cite
|
Sign up to set email alerts
|

A novel geometrical design of gas‐to‐gas planar membrane humidifier for proton electrolyte membrane fuel cells

Abstract: Summary A gas‐to‐gas membrane humidifier recovers heat and water from the wet hot exhaust gas of a proton electrolyte membrane fuel cell and keeps the inlet feed air of the cell warm and humid. This type of humidifier does not need external water sources, and it is compact and efficient with practical applications in portable devices and automobiles. In the present study, four potential designs of gas‐to‐gas planar membrane humidifiers were introduced, and their characteristic behavior was examined. The simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…An overview of the application of CFD models and simulations in the field of membrane technology can be found in [17]. CFD models of flat membrane humidifiers are set up and investigated in different studies and are shown to be an accurate tool to investigate the water transfer in membrane humidifiers [15,16,18,19]. Schmitz et al present a 3D CFD model of a hollow fibre humidifier to analyse the sorption behaviour and the water transport in membrane humidifiers and validate the model with measurement data [20].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the application of CFD models and simulations in the field of membrane technology can be found in [17]. CFD models of flat membrane humidifiers are set up and investigated in different studies and are shown to be an accurate tool to investigate the water transfer in membrane humidifiers [15,16,18,19]. Schmitz et al present a 3D CFD model of a hollow fibre humidifier to analyse the sorption behaviour and the water transport in membrane humidifiers and validate the model with measurement data [20].…”
Section: Introductionmentioning
confidence: 99%